Growing crops for biofuel and forage while conserving soil and water - Evers, Byron J. (Kansas State University, 2012)
The use of renewable feedstocks to produce cellulosic ethanol is quickly becoming a reality as facilities to produce cellulosic ethanol are scheduled to open in the upcoming years. Initial feedstocks for these facilities are thought to be crop residues such as corn (Zea mays L.) and wheat (Triticum aestivum L.) residues. However, additional feedstocks, such as perennial warm-season grasses (WSG), maybe needed to meet the demands of these bioenergy facilities. Thus, the development of regional dedicated energy crop systems is a high priority. Our objectives were to: a) assess the impacts of growing WSG on water storage, soil physical and hydraulic properties, soil organic carbon (SOC) dynamics, and water and wind erosion as compared with row crops, b) assess the impacts of growing WSG on biomass and forage production and quality and c) determine the most adaptable WSG species to dryland conditions. A number of dedicated energy crops and their performance across three different moisture regimes in Kansas were studied. Biomass yield, soil physical and hydraulic properties, and soil water and wind erosion parameters were measured between August 2010 and August 2012. Additionally, forage quality under two cutting systems (biofuel and forage) and two harvest heights (0.1 m and 0.2 m) and water infiltration was determined in 2011. Differences in bulk density, water retention, infiltration and SOC were found to be minimal. However, differences in wind and water erosion parameters indicate that WSG can protect soil from erosion. Furthermore, soil water data indicate that WSG are better suited to use early season moisture to accumulate biomass than annual row crops. Yield results indicate that a two cut hay system with a 0.1 m cutting height can produce more biomass compared with a one cut biofuel system. Additionally, the hay system improved forage quality parameters. Data collected from this project provided insights into the viability of growing various dedicated energy crops across the region during the first five years of production.
Keywords: Switchgrass; Biofuel; Agronomy (0285)